Added phosphorus availability and re-distribution in both natural and cultivated vertisols - Fernandez Lopez, Carolina (2013)
The fates of both native and added phosphorus were studied in a Leptic Hapludert, by Hedley´s fractionation method. The objectives of this study were to: a) assess the reaction of a natural grassland and a cultivated grassland in a Vertisol with added P by fertilization; b) to study the association between inorganic and organic P labile, moderately labile or non-labile forms with P availability for ryegrass growth; c) to test whether ryegrass growth may reflect the effect of a release of P from the soil with the incubation. Soil samples were taken from: a) Natural soil and, b) Cultivated soil that had been fertilized with 120 kg ha-1 yr-1 of TSP. In the laboratory, one group of samples was fertilized with P (0-200 mg P kg-1) and then incubated 25 days at 28 oC. The other group was also fertilized with P but was not incubated. After P fractionation,, ryegrass was grown in a greenhouse 45 days and the dry yield of shoots was measured. Inorganic labile P forms increased with the level of added P in both soils, and these forms were closely associated with ryegrass growth. The inorganic resistant P forms also increased with the level of added P in both soils, but more P was removed from the incubated samples suggesting that part of the added P was redistributed during the incubation. For both soils, the organic labile P decreased with the level of addition in the incubated samples but increased in the non-incubated samples. The organic more resistant P forms did not differ between the natural and cultivated soil and did not show a consistent distribution with added P or incubation. This suggests that these P forms had little influence on P availability in short or medium periods of reaction between soil and P.